Nitric oxide signaling in ctenophores - Moroz, Leonid L.; Mukherjee, Krishanu; Romanova, Daria Y. (Frontiers in Neuroscience, 2023)
Nitric oxide (NO) is one of the most ancient and versatile signal molecules across all domains of life. NO signaling might also play an essential role in the origin of animal organization. Yet, practically nothing is known about the distribution and functions of NO-dependent signaling pathways in representatives of early-branching metazoans such as Ctenophora. Here, we show that NO synthase (NOS) is present in at least eight ctenophore species, including Euplokamis and Coeloplana, representing the most basal ctenophore lineages. However, NOS could be secondarily lost in many other ctenophores, including Pleurobrachia and Beroe. In Mnemiopsis leidyi, a popular reference species, NOS is present both in adult tissues and differentially expressed in later embryonic stages suggesting the involvement of NO in developmental mechanisms. Ctenophores also possess soluble guanylyl cyclases as potential NO receptors with weak but differential expression across tissues. Combined, these data indicate that the canonical NO-cGMP signaling pathways existed in the common ancestor of animals and could be involved in the control of morphogenesis and cilia activities.